Advanced flexible brain‐computer interfaces and devices for the exploration of neural dynamics - Pancheng Zhu; Mengxia Yu; Mingzheng Wu; Yiyuan Yang (Brain-X)
Abstract The rapid advancement of flexible neural interfaces and devices is revolutionizing our ability to explore the neural foundations of consciousness, intelligence, and behavior. Cutting‐edge developments in materials science and system‐level integration are significantly enhancing the spatiotemporal resolution of neural signal acquisition and modulation, paving the way for next‐generation brain‐computer interfaces. These technologies enable unprecedented investigations into the causal relationships between neural dynamics and behaviors in freely moving subjects, offering new insights into various neurocognitive domains. The integration of artificial intelligence and brain organoids with neuroscience research promises to further decode complex neural signals, deepening our understanding of multilevel neural dynamics. Beyond their scientific implications, these innovations also offer transformative possibilities for the diagnosis, treatment, and management of neurological and psychiatric disorders. This perspective paper examines how flexible neural interfaces overcome the limitations of traditional neurotechnology, their potential impact on neural research, and their promising applications in treating neurological and psychiatric disorders, while also considering the ethical implications and future challenges in this rapidly evolving field.